2022
DOI: 10.5005/ijcdas-57-2-91
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Spirometry: Selection of Predicted Values and Defining Abnormality

Abstract: Spirometry is the most frequently performed investigation to evaluate pulmonary function. It provides clinically useful information on the mechanical properties of the lung and the thoracic cage and aids in taking management-related decisions in a wide spectrum of diseases and disorders. Few measurements in medicine are so dependent on factors related to equipment, operator and the patient. Good spirometry requires quality assured measurements and a systematic approach to interpretation. Standard guidelines on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Previous studies have implicated that lung function may theoretically be affected by several directly measured or derived anthropometric variables including standing height, trunk-leg ratio, weight, body surface area, and body mass index. 9 Das and Jahan found that an increase in BSA is associated with an increase in lung volumes and PEFR both in males and females. 10 However, the effect of BSA on the pulmonary functions in patients of silicosis is an arena hardly explored.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have implicated that lung function may theoretically be affected by several directly measured or derived anthropometric variables including standing height, trunk-leg ratio, weight, body surface area, and body mass index. 9 Das and Jahan found that an increase in BSA is associated with an increase in lung volumes and PEFR both in males and females. 10 However, the effect of BSA on the pulmonary functions in patients of silicosis is an arena hardly explored.…”
Section: Discussionmentioning
confidence: 97%
“…Por otro lado, pacientes que acudieron al área de banco de sangre y/o consejería del Hospital Víctor Lazarte Echegaray de la red asistencial Es Salud -La Libertad durante el periodo de recopilación de datos fueron seleccionados como controles, debiendo cumplir con los siguientes criterios de inclusión: Personas de ambos sexos sin patologías pulmonares o respiratorias agudas o crónicas, ni enfermedad pulmonar activa. Para ambos grupos se excluyó a pacientes con diagnóstico previo de Enfermedad Pulmonar Obstructiva Crónica, pacientes Oncológicos, cardiópatas, gestantes, con patologías pulmonares agudas (no más de 2 semanas), con Insuficiencia cardiaca congestiva: NYHA I, II, III y IV, fumadores con un índice de tabaco >10 (26,27) , usuarios de Oxigenoterapia, TBC actual, en UCI, asmáticos o con vasculitis de algún tipo, pacientes con trauma torácico o antecedente similar, con defectos de caja torácica, o patologías diafragmáticas, tiroideas o pleurales. (28,29) A todos ellos, una vez seleccionados, se les solicitó previo consentimiento informado, su participación en el estudio.…”
Section: Materials Y Métodosunclassified
“…These find application in confirmation of diagnosis, evaluation of functional impairment, assessment of therapeutic response, monitoring for occupational and environmental lung damage, pre-operative risk stratification and for following the course of disease. 1 PFTs also find application in studies on public health as well as in settling legal claims for lung injuries. Being non-invasive, relatively less expensive and almost entirely without any hazards to the patient, these tests are also carried out periodically to aid in management decisions.…”
mentioning
confidence: 99%
“…Thus, every person will have a different "normal" value and that is not constant but ever-changing with time. 1 The normal value is calculated using "prediction" equations that take into account the known and the unknown predictors or determinants of the parameter of interest. These equations are developed by studying lung function of a large sample of carefully selected and well-defined "normal" subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation